2021
DOI: 10.1039/d0cs00924e
|View full text |Cite
|
Sign up to set email alerts
|

In situsolid-state nanopore fabrication

Abstract: This review summarises the development of in situ solid-state nanopore fabrication techniques. These techniques are democratising solid-state nanopore research by providing rapid and accessible methods to fabricate nanopores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 191 publications
(292 reference statements)
0
85
0
Order By: Relevance
“…To overcome these issues, a technique called controlled breakdown (CBD) has been developed to fabricate nanopores in solid‐state membranes. [ 29–31 ] In this method, an electric field of ≈0.4–1 V nm −1 is applied across the membrane via the electrolyte solutions whilst simultaneously measuring the resulting current. After a given period, a spike in the current is observed signifying pore formation at which point the voltage is quickly reduced to ensure the fabrication of a small nanopore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these issues, a technique called controlled breakdown (CBD) has been developed to fabricate nanopores in solid‐state membranes. [ 29–31 ] In this method, an electric field of ≈0.4–1 V nm −1 is applied across the membrane via the electrolyte solutions whilst simultaneously measuring the resulting current. After a given period, a spike in the current is observed signifying pore formation at which point the voltage is quickly reduced to ensure the fabrication of a small nanopore.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] However, this requires specialized equipment, trained operators, and is a labor intensive process thus limiting the availability of this technique to the wider research community.To overcome these issues, a technique called controlled breakdown (CBD) has been developed to fabricate nanopores in solid-state membranes. [29][30][31] In this method, an electric Controlled breakdown has recently emerged as a highly appealing technique to fabricate solid-state nanopores for a wide range of biosensing applications. This technique relies on applying an electric field of approximately 0.4-1 V nm −1 across the membrane to induce a current, and eventually, breakdown of the dielectric.…”
mentioning
confidence: 99%
“…Solid-state nanopore can be fabricated using different methods, such as controlled breakdown, electrochemical reactions, laser etching and laser-assisted controlled breakdown [25]. It breaks the limit of natural occurring nanopores and has many advantages, such as very high chemical stability, control of diameter and channel length, adjustable surface properties, and the potential for integration into devices and arrays [26,27].…”
Section: Solid-state Nanoporementioning
confidence: 99%
“…Table 4 summarizes the methods based on the materials used to design the solid-state nanopores. An up-to-date review of in-situ fabrication methods of nanopores can be found in ref [ 105 ].…”
Section: Nanopore Sensorsmentioning
confidence: 99%